2013
DOI: 10.1074/jbc.m112.440693
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Movements of Eukaryotic Translation Initiation Factors eIF1, eIF1A, and eIF5 Trigger Phosphate Release from eIF2 in Response to Start Codon Recognition by the Ribosomal Preinitiation Complex*

Abstract: Background: Start codon recognition triggers eIF1 and P i release from the preinitiation complex. Results: The C-terminal tail of eIF1A moves closer to eIF5 upon start codon recognition, and this movement is required for P i release. Conclusion: eIF1 release and movement of the eIF1A C-terminal tail toward eIF5 are coupled processes. Significance: Start codon recognition induces coordinated movements of initiation factors that trigger downstream events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
127
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(142 citation statements)
references
References 44 publications
14
127
0
1
Order By: Relevance
“…28,63,64 It also plays a role, along with eIF5B, in ensuring proper subunit joining and formation of elongation-competent 80S ribosomes. 28,63,64 Hydroxyl radical probing and structural modeling involving eIF1A and Tetrahymena thermophila 40S ribosomal subunits (based on bacterial 30S:IF1 complex information) at »3.9A suggested that eIF1A resides near the A-site and makes contacts with eukaryotespecific proteins eS27 and eS30 as well as conserved protein uS12 which harbors eukaryote-specific extensions. 15,65 However, direct involvement of uS12 eukaryote-specific extensions in eIF1A binding has not been proven yet.…”
Section: E999576-6mentioning
confidence: 99%
“…28,63,64 It also plays a role, along with eIF5B, in ensuring proper subunit joining and formation of elongation-competent 80S ribosomes. 28,63,64 Hydroxyl radical probing and structural modeling involving eIF1A and Tetrahymena thermophila 40S ribosomal subunits (based on bacterial 30S:IF1 complex information) at »3.9A suggested that eIF1A resides near the A-site and makes contacts with eukaryotespecific proteins eS27 and eS30 as well as conserved protein uS12 which harbors eukaryote-specific extensions. 15,65 However, direct involvement of uS12 eukaryote-specific extensions in eIF1A binding has not been proven yet.…”
Section: E999576-6mentioning
confidence: 99%
“…One possibility would be that eIF2β-S264Y prevents the eIF2β-NTT from releasing eIF1 and binding to the eIF5-CTD, which should impede dissociation of eIF1 from the PIC (Fig. 1A; Nanda et al 2013). However, interaction between the eIF2β zinc-binding domain and its NTT has not been reported, and it is also unclear why this would happen at AUG, but not at UUG, start codons.…”
Section: Martin-marcos Et Almentioning
confidence: 99%
“…Thus, eIF1 performs a dual function in the scanning mechanism of promoting rapid TC loading in the P OUT configuration while impeding rearrangement to the more stable P IN state until an AUG codon is recognized by Met-tRNA i (Fig. 1A;Hinnebusch 2011;Nanda et al 2013). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once AUG recognition and codon-anticodon base-pairing has been established, the eIF5 carboxy moiety promotes the dissociation of eIF1, together with inorganic phosphate derived from the GTP hydrolysis of the ternary complex (Cheung et al 2007;Luna et al 2012). In addition, the eIF1A carboxy terminus moves closer to the eIF5 amino terminus (Nanda et al 2013). This movement is coupled to eIF1 exit, which leaves the P site free and allows tighter binding of the initiator tRNA at this site.…”
Section: Introductionmentioning
confidence: 99%